STUDIES OF ENVIRONMENTAL IMPACTS ON OPEN-AIR DUMPS IN RURAL LOCATIONS IN THE MUNICIPALITY OF PARINTINS/AM - da Silva, Charlene Maria Muniz; dos Santos, Alem Silvia Marinho; Ribeiro, Edinelza Macedo; da Silva, Idelcy Souza; da Silva, Jennifer Melo; Cruz, Fernanda da Costa (Seven Editora, 2025)
This article investigates the environmental impacts of "junk dumps" in rural areas of the municipality of Parintins - AM, focusing on the rural locality of Zé Açu. The junk dump represents a significant environmental problem in rural areas, where the improper disposal of waste causes a negative impact on the environment and people’s quality of life. To carry out this study, we applied the inductive method, with techniques such as questionnaire application, on-site observation, handling of geotechnologies, with Drone and Gps (Global Positioning System) and geoprocessing programs, to map, analyze and locate the dumps. It was found that the community of Bom Socorro do Zé Açu faces a great challenge in relation to junk dumps, which causes problems both in the environment and also for the public health of local residents, with the dumping of solid waste in areas close to the community. These cause great impacts to local residents, such as on the soil, watercourse near these addicted dumps, as well as impact the ecological cycle of animals and plants, in addition to attracting disease vectors, such as rats, flies, cockroaches, and others. We emphasize that it is essential that there is an integrated and adequate management of solid waste in this location, including collection, awareness of residents and appropriate treatment of garbage, to minimize these impacts and promote a healthier and more sustainable environment in these rural communities in the municipality of Parintins -AM. DOI: https://doi.org/10.56238/sevened2025.021-015